Analisis Metode Pembelajaran Inovatif dalam Pembelajaran Tematik Sekolah Dasar dan Pengaruhnya Terhadap Hasil Belajar Siswa: Penelitian - Wafiq Nur Azizah; Devy Herlina Pranadita; Naomi Srikandhi; Fatimah Mitsaini; Uswatun Hasanah; Taufik Muhtarom (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Thematic learning strategies that integrate various subjects holistically are an effective approach, but their success is largely determined by the learning methods used by teachers. Innovation in learning methods is needed that can encourage active student involvement, in-depth understanding of the material, and comprehensive character development. This study aims to: (1) explore various types of innovative methods suitable for thematic learning at the elementary school level; (2) examine how teachers implement methods in the classroom; and (3) determine the effect of learning methods on student learning outcomes. This study uses a qualitative approach with the Systematic Literature Review (SLR) method. Data were obtained from searching scientific articles through the Google Scholar, Garuda, and SINTA databases, with the criteria of SINTA-indexed journals and published between 2020 and 2025. A total of 27 articles that met the criteria were analyzed using a thematic approach to identify dominant patterns in the application of innovative learning methods. The results of the study indicate that methods such as project-based learning, problem-based learning, and discovery learning. The implementation of these methods with the role of facilitator, learning experience designer, and student exploration companion in the classroom.